Financial trouble across generations: Evidence from the universe of personal loans in Denmark - Claus Thustrup Kreiner; Søren Leth-Petersen; Louise C. Willerslev-Olsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2017)
Do people end up in financial trouble simply because of adverse shocks to income and wealth, or is financial trouble related to persistent differences in financial attitudes and behavior that may be transmitted from generation to generation? We address this question using a new administrative data set with longitudinal information about defaults for the universe of personal loans in Denmark. We provide non-parametric evidence showing that the default propensity is more than four times higher for individuals with parents who are in default compared to individuals with parents not in default. This intergenerational relationship is apparent soon after children move into adulthood and become legally able to borrow. The intergenerational relationship is remarkably stable across age groups, levels of loan balances, parental income levels, childhood school performance, time periods and different measures of financial trouble. Basic theory points to three possible explanations for the correlation across generations in financial trouble: (i) children and parents face common shocks; (ii) children and parents insure each other against adverse shocks; (iii) financial behavior differs across people and is transmitted across generations. Our evidence indicates that the last explanation is the most important. Finally, we show that the intergenerational correlation in financial trouble is not fully incorporated in interest setting on loans, pointing to the existence of an interest rate externality in the market for personal loans.
Keywords: D12; D91; G20; 330; Household borrowing decisions; default; intergenerational dependency